Antibiotic prescription patterns in Spanish cystic fibrosis patients: results from a national multicenter study - Concepción Prados; Juan de Dios Caballero; Rosa Girón; Rosa del Campo; María-Isabel Barrio; Antonio Salcedo; Rafael Cantón (Farmacia Hospitalaria)
Objective: Information about antibiotic prescription patterns for cystic fibrosis (CF) patients and, specifically, about inhaled treatment strategies for their management is lacking in Spain due to the absence of a national patient registry. In this study we present data about antibiotic prescription in the Spanish CF context that were obtained in a multicenter study, being inhaled treatment strategies the special focus of this work. Methods: Twenty-four specialized CF units (12 adult, 12 pediatric) from 17 tertiary- care hospitals covering all Spanish Autonomous Communities provided sputa and clinical data from 15 consecutive patients. Data about antibiotic and non-antibiotic therapies prescribed to these patients during the year prior inclusion (2013) were retrospectively collected. Results: The multicenter study included 341 CF patients from all age groups and clinical status. The prevalence of oral, inhaled and intravenous therapies was 89% (n = 302), 80% (n = 273) and 31% (n = 105), respectively. The most prevalent oral agents were ciprofloxacin (n = 177, 59%), cotrimoxazole (n = 109, 36%) and amoxicillin-clavulanate (n = 99, 33%), whereas ceftazidime (n = 53, 50%), tobramycin (n = 43, 41%) and meropenem (n = 41, 49%) were the most prevalent intravenous ones. Two or more different inhaled antibiotics were administered to 67 patients (24%), 51 of them receiving 2 drugs continuously in alternating schemes. Nebulization of intravenous specific antibiotics was common (n = 39) and, in some cases, was used for maintenance purposes. Conclusions: These results show that the treatment of CF patients is evolving more rapidly than clinical consensus guidelines. Clinical trials evaluating new specific inhaled combinations and new alternative treatment regimes of the existing ones are needed.